Majeed Amjad: Wonderer of Earth - Ghulam Fareed Hussaini (بازیافت, 2017)
Urdu poetry before Maulana Altaf Hussain Hali's "Muqadma Sher o shairy" traditionally was known by its sterio-type rules. Hali and Azad encouraged the new ideas to expand urdu language and in general and poetry and particular. Accordingly new apporach of criticism recognized Nazir Akber Abadi. Majeed Amjad accepted the new parameters of peotry and painted all creatures and objects of nature in his poetry. Civilizations consist not only of human being but all the lives and material of soil. He gave the importance not only to the drpressed people of society but animals i.e sheep, cow, sparrow etc.This article is an attempt to explore the aspect of Majeed's poetry which potray the caricature of culture and civilization.